Consistency of Self-Reported Alcohol Consumption on Randomized and Sequential Alcohol Purchase Tasks - Amlung, Michael; MacKillop, James (Frontiers in Psychiatry, 2012)
Behavioral economic demand for addictive substances is commonly assessed via purchase tasks that measure estimated drug consumption at a range of prices. Purchase tasks typically use escalating prices in sequential order, which may influence performance by providing explicit price reference points. This study investigated the consistency of value preferences on two alcohol purchase tasks (APTs) that used either a randomized or sequential price order (price range: free to 30 per drink) in a sample of ninety-one young adult monthly drinkers. Randomization of prices significantly reduced relative response consistency (p < .01), although absolute consistency was high for both versions (>95%). Self-reported alcohol consumption across prices and indices of demand were highly similar across versions, although a few notable exceptions were found. These results suggest generally high consistency and overlapping performance between randomized and sequential price assessment. Implications for the behavioral economics literature and priorities for future research are discussed.